Implementation of guaranteed services in the MANGO clockless network-on-chip - Bjerregaard, T.; Sparsø, J. (IEE proceedings. Computers and digital techniques, 2006)
Shared, segmented, on-chip interconnection networks, known as networks-on-chip (NoC), may become the preferred way of interconnecting intellectual property (IP) cores in future giga-scale system-on-chip (SoC) designs. A NoC can provide the required communication bandwidth while accommodating the effects of scaling microchip technologies. Equally important, a NoC facilitates a truly modular and scalable design flow. The MANGO (message-passing asynchronous network-on-chip providing guaranteed services over open core protocol (OCP) interfaces) NoC is presented, and how its key characteristics (clockless implementation, standard socket access points, and guaranteed communication services) make MANGO suitable for a modular SoC design flow is explained. Among the advantages of using clockless circuit techniques are inherent global timing closure, low forward latency in pipelines, and zero dynamic idle power consumption. Time division multiplexing, generally used to provide bandwidth guarantees in clocked NoCs, however, is not possible in a clockless environment. MANGO provides an alternative, high-performance solution to providing hard, connection-oriented service guarantees, using clockless circuit techniques. In-depth circuit details are presented, and the 0.13mum standard cell implementation of a 5X5 routing node, for use in a mesh type NoC, is described.